2017
DOI: 10.1115/1.4036468
|View full text |Cite
|
Sign up to set email alerts
|

Passive Control of Piston Secondary Motion Using Nonlinear Energy Absorbers

Abstract: The impulsive behaviour of the piston in the cylinder liner plays a key role in the Noise, Vibration and Harshness (NVH) of internal combustion engines. There have been several studies on the identification and quantification of piston impact action under various operation conditions. In the current study, the dynamics of the piston secondary motion are initially explored in order to describe the aggressive oscillations, energy loss and noise generation. The control of piston secondary motion (and thus, impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The oil film force and moment are nonlinear components due to the nonlinear pressure distribution. 31,32 The lubrication model between the piston and liner is always considered to be the hydrodynamic lubrication model, according to the average flow model that was established by Patir and Cheng. 30 When the effect of the surface wave on the lubrication is considered, the average Reynolds equation between the piston skirt and liner is written as follows…”
Section: Hydrodynamic Lubrication Modelmentioning
confidence: 99%
“…The oil film force and moment are nonlinear components due to the nonlinear pressure distribution. 31,32 The lubrication model between the piston and liner is always considered to be the hydrodynamic lubrication model, according to the average flow model that was established by Patir and Cheng. 30 When the effect of the surface wave on the lubrication is considered, the average Reynolds equation between the piston skirt and liner is written as follows…”
Section: Hydrodynamic Lubrication Modelmentioning
confidence: 99%
“…Recently, studies have focused on the external periodic forcing of the primary system in conjunction with the NES [14,20].…”
Section: S Theodossiades Cnd-17-1339mentioning
confidence: 99%
“…Recent studies [6][7][8][9][10][11] have revealed the potential of using nonlinear vibration absorbers (nonlinear energy sinks (NES)) with low mass and inertia properties for effectively attenuating the generation and propagation of powertrain torsional oscillations. The NES possesses essentially nonlinear stiffness and, thus, instead of being tuned to a preferential frequency, it is activated by the energy input.…”
Section: Introductionmentioning
confidence: 99%